Age and pattern of cervical smear cytology in Federal Medical Centre Asaba – a five year review - Daniel Nnaemeka Onwusulu; Samuel okwuchukwu ilikannu; Chikodili Ogugwa Ochuba; Valentine Idama; Emmanuel Egboduku; Adeniyi Johnson Fagbemi; Sunday Emmanuel Jombo (Advances in Medical, Pharmaceutical and Dental Research)
Background: Cancer of the cervix is a leading cause of cancer deaths among women in low middle income countries. Screening for premalignant lesions of the cervix, using cervical smear is preventive. The pattern of cytological findings varies with age , this pattern is not well known in our environment. Objective: To assess the pattern of cervical smear cytology in Federal Medical Centre, Asaba. Methods: This was a retrospective descriptive study of all cervical smears received and processed at the histopathology department of the Federal Medical Centre (FMC), Asaba between 1st January 2016 and 31st December 2020. Those with inadequate data were excluded from the study. Classification was by the 2014 Bethesda system. Data collected was analyzed using the SPSS (IBM version 20) and results presented in frequencies, percentages and tables. Results: A total of 1184 cervical smear samples were received in the histopathology department of FMC, Asaba during the period of study. One thousand one hundred and fifty were satisfactory. The mean age was 43+/-10.58 and ranges between 19 and 76years. The age group with the largest number of cervical smears was 41-50years (412; 35.8%). About 807(70.2%) were normal smears while 343(29.8%) had abnormal results. Of the abnormal results 173(15.0%) were negative for intraepithelial cell abnormalities while 170(14.8%) had intraepithelial cell abnormalities. Of these were ASC-US (13; 1.1%), LSIL (129; 11.2%), HSIL (28; 2.4%). The prevalence of HSIL increased with age; the highest was >60 years (35.7%).The reverse was the case for the lower grade lesions. There was a significant relationship between the ages of the patient and the pattern of cervical smear results (P= < 0.01). Conclusion: Population screening programs should be encouraged for the inclusion of younger women in whom lower grade lesions are commoner to reduce the prevalence of cervical cancer in our population.   Received on, 30 January 2025 Accepted on, 17 March 2025 Published on, 14 April 2025